PENGARUH TEKNIK MODELING SIMBOLIK TERHADAP PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK KELAS X TKI 1 SMK NEGERI 3 MADIUN - Setyoningrum, Wahyu Cahya; Trisnani, Rischa Pramudia; Sari, Qonik Kus Armanda (Jurnal Muria Research Guidance and Counseling (MRGC), 2024)
Learning motivation is one of the things that needs to be considered in learning because there are still many who think that motivation is not that important to improve learning achievement. The aim of this research is to study the effect of symbolic modeling techniques in guidance and counseling services on increasing students' learning motivation. This technique is a method in guidance and counseling services that uses pictures, videos or other stories to help students understand the concept of learning motivation. This research uses a guidance and counseling action research approach which involves several cycles, namely planning, action, observation and reflection. The research subjects were class X TKI 1 students at SMK Negeri 3 Madiun with low learning motivation. Data was collected from observations, interviews and special questionnaires regarding learning motivation before and after the intervention.The research results showed that students learning motivation improved significantly after intervention with symbolic modeling techniques.